Eksistensi Pasar Media di Indonesia: Studi pada Bisnis Media Indosiar - Holil, Muhammad; Kinanti, Deo Gratias (Mahesa Research Center, 2023)
This article aims to analyze the existence of the media market in Indonesia with a case study on the Indosiar media business. The problem is how Indosiar can still exist considering that there are already many TV stations that have mushroomed in the Indonesian television industry? And what is Indosiar's strategy to run its business in the midst of this intense competition? In order to approach this problem, it is used as a reference for media economic theory. The data were collected through interviews and documentation obtained from the media, both print media and internet media and analyzed qualitatively. This study concludes that Indosiar can still exist despite the proliferation of TV stations in the Indonesian television industry. In order for its existence to continue, Indosiar targets the family or family segment, cares about variety show programs so that the lower and upper middle class people can reach, and presents soap opera programs targeting housewives. Indosiar's strategy to keep the media business going is to determine the target audience and develop a flagship program. Its flagship program is tailored to the interests and needs of the audience. With the accuracy of this strategy, the audience will see a lot and Indosiar will earn revenue from advertising contracts that are broadcast.